Inovasi Kemasan yang Komunikatif dan Edukatif untuk Cold-Pressed Juice di Surabaya - Cinthya Noviana; Christian Anggrianto (Jurnal Vicidi, 2018)
The purpose of this research is to know the appropriate communicative and educative packaging and labeling for cold-pressed juice product in Surabaya. The research method used in this research are qualitative and quantitative research methods. Qualitative research methods includes interviews with resource persons and product users (extreme users and expert users) as well as literature studies of scientific books and journals related to nutrition, food labels / nutrition facts. Quantitative research methods are used by distributing online questionnaires to 120 prospective target market who domiciled in Surabaya and its surrounding areas. The conclusion of this research is the need for cold pressed juice products that are packaged and designed in a modern way to communicate the nutritional content and benefits of cold pressed juice products in Surabaya.